Is there a correlation between blood glucose curve and the insulin resistance during oral glucose tolerance test in females suffering from polycystic ovary syndrome? - Spremović Radjenović, Svetlana; Pupovac, Miljan (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Insulin resistance occurs in approximately 60–80% of women with polycystic ovary syndrome (PCOS) and in 95% of obese women with PCOS. Previous studies have shown that the shape of the glucose curve obtained during an oral glucose tolerance test (OGTT) may be useful as a metabolic screening parameter and could give insight into the future risk of diabetes mellitus type II. The aim of this study was to determine the frequency of insulin resistance according to the Homeostasis model assessment of insulin resistance (HOMA-IR) and indirect assessment method of insulin resistance based on insulinemias during the oral glucose tolerance test (OGTT) (here in after “insulinemias during the OGTT”), as well as, frequency of glucose curve shapes (monophasic, biphasic, triphasic) in patients with PCOS. Also, the aim of research was testing the correlation between glucose curve shape and peak time of glucose during the OGTT with presence of insulin resistance in patients with PCOS. Methods. Patients were observed according to the following parameters: presence of insulin resistance, glucose curve shape and peak time of glucose and insulin during the OGTT. Results. The observed prevalence of insulin resistance in the PCOS group according to the HOMA-IR > 2.5 was 66.19% and according to insulinemias during the OGTT was 78.42%. The shape of the glucose curve was monophasic in 293 (70.26%), biphasic in 56 (13.43%) and triphasic in 68 (16.31%) of patients. There was statistically significant difference in the frequency of insulin resistance, according to glucose curve shape, only when it was defined by insulinemias during the OGTT (p = 0.005). Conclusion. According to results of the study, the most patients with PCOS have a monophasic shape of glucose curve. When we take frequency of insulin resistance in account, we notice approximately the same frequency in all types of curves, when it is defined by the HOMA-IR. On the other hand, when insulin resistance is defined by insulinemias during the OGTT, resistant patients with PCOS mostly have triphasic glucose curve shape.
Keywords: polycystic ovary syndrome; glucose tolerance test; blood glucose; insulin resistance